Strategi Pengembangan Karir Dosen dalam Peningkatan Motivasi dan Kepuasan Kerja di Universitas Sawerigading Makassar - Besse Wulandari Aziz; Muhammad Syukur; Firdaus W. Suhaeb (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Lecturer career development will bring lecturer satisfaction so that it will have an impact on improving the quality of learning. Lecturers as professional educators and scientists with the main task of transforming, developing, and disseminating science and technology through education, research, and community service. The quality of learning cannot be separated from the quality of Human Resources itself, namely the quality of the lecturers. Likewise, the quality of lecturers will determine the quality of graduates that will be produced. This study aims to analyze the career development strategy of lecturers in increasing motivation and job satisfaction within the scope of Sawerigading University Makassar. This study uses a qualitative research method based on a literature review. The results of the study state that Lecturer career development is a process that must be carried out continuously so that lecturers' careers can be brilliant in the future, where improving lecturers' careers can also have an impact on improving the quality of learning, in developing lecturers a strategy is needed so that lecturers' careers can continue to develop. which makes lecturers more motivated to carry out the tridharma of higher education. So that the quality of learning will increase and lead to quality graduates.